SUBACUTE (4-WEEKS) FORMALDEHYDE INHALATION CHANGES SOME ENZYME ACTIVITIES PARTICIPATING IN IMPORTANT METABOLIC PATHWAYS IN RAT LIVER - Yılmaz, H. Ramazan; Özen, O. Aslan; Özyurt, Hüseyin; Söğüt, Sadık; Songur, Ahmet; Sarsılmaz, Mustafa (Fırat University, 2002)
Aim: The aim of this study was to evaluate whether some enzyme activities are changed in the liver of rats exposed to subacute formaldehyde (FA) inhalation (4-weeks). Material and Methods: Thirty male albino Wistar rats were divided into 3 groups randomly (10 for each group). The first group of rats were used as control. Rats were exposed to the atmosphere containing 10 and 20 ppm FA continuously (8 hours per day, 5 days per week) in Groups I and II. Hexokinase (HK), malate dehydrogenase (MDH), lactate dehydrogenase (LDH), glucose-6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD) activities were measured in the liver tissues. Results: The results showed a remarkable reduction of G6PD activity in the liver tissues from rats exposed to 10 ppm FA for 4-weeks. There were no differences in the activities of HK, 6PGD, MDH, and LDH among study and control groups. It was observed that the G6PD activity reduced and MDH activity increased in liver tissues from rats exposed to 20 ppm FA for 4-weeks. But, there was no difference in activities of HK, 6PGD, and LDH. Conclusions: FA, as an environmental toxic substance, may interrupt the antioxidant system in liver by blockage the pentose phosphate pathway.

Amaç: Bu çalışmanın amacı; subakut (4 hafta) dönemde solunan formaldehitin (FA) sıçan karaciğerindeki bazı enzim aktivitelerini değiştirip değiştirmediğini ortaya koymaktır. Gereç ve yöntem: 30 adet erkek albino Wistar cinsi sıçanlar 3 gruba rasgele eşit olarak ayrıldı. İlk grup kontrol ayrılıp, diğer sıçanlara sırasıyla 10 (Grup II) ve 20 (Grup III) ppm. hava ile karışık FA gazı (8 saat/gün; 5 gün/hafta; 4 hafta) verildi. Karaciğer dokularında; hegzokinaz (HK), malat dehidrogenaz (MDH), laktat dehidrogenaz (LDH), glukoz-6-fosfat dehidrogenaz (G6PD) ve 6-fosfoglukonat dehidrogenaz (6PGD) enzim aktiviteleri ölçüldü. Bulgular: 10 ppm. FA soluyan gruba ait karaciğer G6PD aktivitesinde önemli miktarda bir azalma görüldü. HK, 6PGD, MDH ve LDH seviyelerinde ise kontrol grubu ile karşılaştırıldığında bir fark görülmedi. 20 ppm. FA soluyan grupta; G6PD aktivitesinde azalma, MDH aktivitesinde artma tespit edildi. HK, 6PGD ve LDH aktivitelerine ise bir fark bulunamadı. Sonuç: Çevresel toksik bir madde olan FA pentoz fosfat yolunu bloklayarak karaciğer antioksidan sisteminde kesintiye sebep olabilir.
SUBACUTE (4-WEEKS) FORMALDEHYDE INHALATION CHANGES SOME ENZYME ACTIVITIES PARTICIPATING IN IMPORTANT METABOLIC PATHWAYS IN RAT LIVER